Obtenção das curvas de torque e potência de um motor 2 tempos de 10CC por meio de uma bancada híbrida - Carvalho, Prince Azsembergh Nogueira de (Universidade Federal Rural do Semi-Árido, 2018)
Performance is the main commercial area for an aircraft, which highlights the performance of the aircraft by engines and these, with the available torque and availability. This work was to be used in the score of torque and character performance in the loop of propellers tested. It was built and built on a hybrid steel bench, to couple the engine and the data acquisition system through the Arduino® platform with a load cell and an amplifier module. There have been two variations of steps and equal diameters, which are generally used in the engine tested. The moment of inertia of the propellers (complex bodies) was mediated by the use of the experimental torsion pendulum method. A pickup was used to promote the airflow by simulating a wind tunnel. A rotation has been captured for the air flow range from where the motor generally operates, and data is sent via Arduino®. Torque and power curves were raised, where the APC 12x4 propeller proved to be more promising, providing greater torque and power at a higher angular velocity of operation. A built-in bench proved to be versatile in the characterization of 10cc engines, and an applied methodology was constructed satisfactorily, based on its own application model and simplicity of performing the tests.
Monografia
Keywords: Motor; Bancada Híbrida; Potência; Torque; Rotação; Engine; Hybrid Workbench; Power; Torque; Rotation; ENGENHARIAS::ENGENHARIA MECANICA